Perancangan Visual Branding Desa Wisata Green Talao Park Pariaman sebagai Media Penguatan Citra, Identitas, dan Daya Saing Destinasi Wisata - Trisnawati, Desi; Ananta, Aryoni; Hendra, Hendra; Ediantes, Ediantes (JOM, 2026)
This study aims to design a visual branding system for Green Talao Park (GTP) Ulakan Tourism Village as a strategic medium to strengthen destination image, identity, and competitiveness. The research employs a qualitative approach using participant observation, in-depth interviews, and literature review to explore local potentials and define the visual characteristics of the destination. The findings reveal that the absence of a structured visual identity has limited the optimization of GTP Ulakan’s tourism potential. By integrating local genius elements such as mangrove ecosystems, talao landscapes, and coastal scenery, this study produces a distinctive and contextual visual branding system. The resulting logo and visual identity demonstrate key branding principles, including differentiation, consistency, flexibility, and cross-media applicability. The implementation of branding across souvenirs and promotional media enhances brand awareness, strengthens destination positioning, and fosters symbolic attachment between visitors and the place. This study contributes to the development of destination branding discourse by emphasizing the importance of local-based visual identity in supporting sustainable tourism and community-based economic growth.